2004
DOI: 10.1159/000081328
|View full text |Cite
|
Sign up to set email alerts
|

Expression of UDP-GalNAc:Polypeptide N-Acetylgalactosaminyltransferase-12 in Gastric and Colonic Cancer Cell Lines and in Human Colorectal Cancer

Abstract: Objective: The expressionofUDP-GalNAc:polypeptide N-acetylgalactosaminyltransferase-12 (pp-GalNAc-T12) was studied in 3 normal human tissues (stomach, small intestine and colon), 3 stomach and 6 colon cancer cell lines, as well as in the resected cancer tissues and normal tissues (control) from 19 patients with colorectal cancer. Methods: Marathon Ready® cDNAs were used as the templates of normal tissues. mRNA was extracted from the cell lines and resected tissues, and reverse-transcribed to cDNA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Genetic screening of cancer patients is also revealing potential contributions of O-glycosylation pathways to cancer. For example, inherited deleterious variants in GALNT12 are associated with susceptibility to colorectal cancer [129], consistent with earlier studies that expression of GALNT12 seems to be a negative marker especially of metastatic gastric and colorectal cancer [130]. Somatic and germ-line mutations in GALNT12 have been identified in individuals with colon cancer [131].…”
Section: Tn and Stn Antigens In Colorectal Cancer (Crc)supporting
confidence: 79%
“…Genetic screening of cancer patients is also revealing potential contributions of O-glycosylation pathways to cancer. For example, inherited deleterious variants in GALNT12 are associated with susceptibility to colorectal cancer [129], consistent with earlier studies that expression of GALNT12 seems to be a negative marker especially of metastatic gastric and colorectal cancer [130]. Somatic and germ-line mutations in GALNT12 have been identified in individuals with colon cancer [131].…”
Section: Tn and Stn Antigens In Colorectal Cancer (Crc)supporting
confidence: 79%
“…Specific ppGalNAc Ts have also been linked to Williams-Beuren syndrome (WBSCR17, pt-GalNAc-T, or GALNTL3) (38,39) and hereditary multiple exostoses (ppGalNAc T5) (40). Genomewide sequencing studies have also revealed biochemically inactivating germ lines and somatic mutations in GALNT5 and GALNT12 (ppGalNAc T5 and T12) in individuals with breast and colon cancers (41,42) consistent with previous studies (43). Other genome-wide association scans suggest that GALNT2 (ppGalNAc T2) variants may be associated with levels of HDL cholesterol and coronary artery disease (44 -46).…”
supporting
confidence: 69%
“…It is well known that oncogenesis up-regulates the expression of N-glycans (13). In addition, ␣-fucosylation was observed in several types of tumors, including colorectal, hepatoma, ovarian, lung, and thyroid (52)(53)(54)(55)(56), and it is correlated with tumor metastasis, disease recurrence, and poor survival of patients (56). Together, our results show that changes in the glycophenotype observed during EMT are consistent with changes described in the literature; thus, EMT is an applicable model to study metabolic and glycophenotype changes during carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%